ANALISIS FAKTOR-FAKTOR EKONOMI MAKRO DAN KOMPONEN TINGKAT KESEHATAN BANK TERHADAP HARGA SAHAM BANK KBMI 3 DAN KBMI 4 - Elsha Widya Salmah (2023)
This study aims to determine the factors that influence the stock prices of KBMI 3 and KBMI 4 banks. This research uses 4 groups of core capital banks (KBMI) 3 and 4 groups of core capital banks (KBMI) 4 as research objects including Bank Mandiri, Bank Negara Indonesia, Bank Central Asia, Bank Rakyat Indonesia, Bank Permata, Bank CIMB Niaga, Bank Pan Indonesia and Bank Danamon. Sampling used a purposive sampling technique for the 2010-2021 period. The data used uses secondary data. The hypothesis test in this study used panel data regression analysis techniques with the E-views 10 program and a significance level of 0.05 (5%). The results of partially testing the hypothesis that interest rates and capital adequacy ratio (CAR) have no effect on the stock prices of KBMI 3 and KBMI 4 banks. Partially world crude oil prices and return on assets (ROA) have an effect on stock prices of KBMI 3 and KBMI banks 4. Simultaneously the four variables affect the stock prices of KBMI 3 and KBMI 4 banks.